Faktor-faktor yang berhubungan dengan Usia Menarche Siswi SMP PGRI Pekanbaru - Novita Lusiana (Jurnal Kesehatan Komunitas, 2012)
Some recent research suggests the likelihood of an accelerated teenage girls experience menarche, which means the faster entering the reproductive period. The purpose of this study to determine the factors associated with age of menarche girls, including maternal age of menarche, nutritional status and socioeconomic status. This study uses quantitative analytical methods, with cross sectional design, are carried out from March-April 2012 in Junior High School PGRI Pekanbaru. Sampling technique is done by simple random sampling simple random The subject of this study was grade VII and VIII SMP PGRI Pekanbaru numbered 62 people. Measuring instrument used was quesionnaire. Data for bivariate analysis with ChiSquare test. The results obtained most of the girls experienced menarche at normal age of female students by 43 people (69.4%), women who experienced menarche at normal age of mothers was 49 students (79.0%), with significantly by 0.015 (p value <0, 05) with OR = 5,52. Normal nutritional status of as many as 48 students (77.4%), with significantly by 0.022 (p value <0.05) with OR=4,48 and high socioeconomic status of 40 female students (64.5%), amounting to 0.004 exhibited significantly (p value <0, 05 )with OR = 5,65. It is expected to work with officers Care Health Services Youth (PKPR) from the local health center to provide counseling on reproductive health, especially adolescents aged 12-18 years of menarche